Diseño y aplicación de una guía de trabajo, para el correcto proceso de enseñanza aprendizaje del mini basquetball para niños de 5 a 6 años de la Unidad Educativa La Inmaculada de la cuidad de Latacunga, provincia de Cotopaxi, durante el año 2012 - 2013 - Herrera Torres, Leandro Rodrigo (2015)
In conducting this research work was determined as object of study the process of learning the Mini Basquetball that was aimed at the design and development of a guide for sport initiation included ages 5-6 years. The practice of sport leads to improved child behavior, to have an chaired by rules and regulations that directly influence their behavior life. The Mini Basquetball, used to go motivating children to sports and the development of all its physical and volitional capacities. The Mini Basquetball Basketball is a form adapted for the game among children. The dimensions of the field, the height of the rings, the size of the boards and the diameter and weight of the balls are adapted to age. Team sports are characterized, among other things, the wealth of situations that provide a training medium par excellence in so far as is practical, when properly oriented induces the development of skills in multiple planes as the tactical-cognitive, technical and affective partner....